A case of Behcet's disease with upper extremity thrombosis - Albay, Ayşegül; Kanatsız, Büşra; Platin, Ayşe Rana; Sali Çakır, Hacer; Oludağ, Gülay; Basat, Sema (Journal of Surgery and Medicine, 2018)
Behcet's disease (BD) isa multi-system vasculitis in which recurrent oral and genital ulcers, uveitisas well as musculoskeletal, neurologic and gastrointestinal system involvementare observed. In previous studies, vascular involvement rate ranges between1-38%. Most common vascular complication is superficial vein thrombosis of theextremities, followed by deep vein thrombosis. In this study, we will present acase of BD with upper extremity thrombosis.